2007
DOI: 10.1038/sj.mp.4001991
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dissection of NRG1-ERBB4 signaling implicates PTPRZ1 as a potential schizophrenia susceptibility gene

Abstract: Neuregulin and the neuregulin receptor ERBB4 have been genetically and functionally implicated in schizophrenia. In this study, we used the yeast two-hybrid system to identify proteins that interact with ERBB4, to identify genes and pathways that might contribute to schizophrenia susceptibility. We identified the MAGI scaffolding proteins as ERBB4-binding proteins. After validating the interaction of MAGI proteins with ERBB4 in mammalian cells, we demonstrated that ERBB4 expression, alone or in combination wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
59
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 83 publications
(109 reference statements)
8
59
2
Order By: Relevance
“…In this study, we could not replicate a previous report [Buxbaum et al, 2007], which revealed a significant association between PTPRZ1 and schizophrenia in a Caucasian population. The discrepancy between Japanese and Caucasian populations may derive from ethnic differences in the etiology of schizophrenia.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In this study, we could not replicate a previous report [Buxbaum et al, 2007], which revealed a significant association between PTPRZ1 and schizophrenia in a Caucasian population. The discrepancy between Japanese and Caucasian populations may derive from ethnic differences in the etiology of schizophrenia.…”
Section: Discussioncontrasting
confidence: 99%
“…Then we defined 28 tagging SNPs (Table I) with the criterion of an r 2 > 0.8 in 'pair-wise tagging only' mode using the 'Tagger' program, implemented by Haploview software version 4.0 (http://www.broad.mit.edu/mpg/haploview/index.php) [Barrett et al, 2005;de Bakker et al, 2005], considering two points in particular. First, we mandatorily included marginal and significant SNPs reported in previous study (Table I; rs6466808, rs10278079, rs1196471, rs2693657, rs1147502, rs1147497, rs1147489, and rs1206381; indicated by asterisk) as tagging SNPs, except for rs1196513 and rs13241278 [Buxbaum et al, 2007]. Because rs1196513 and rs13241278…”
Section: Tagging Snp Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the soluble PTP-isoform has been shown to be necessary for maturation of oligodendrocyte progenitors to differentiated myelin-secreting oligodendrocytes in vitro (77), and PTP--deficient mice exhibit increased myelin breakdown (78). In addition, the PTPRZ1 gene in humans is a schizophreniasusceptibility gene (79), and PTP-regulates tyrosine phosphorylation of voltage-gated sodium channels in neurons (80). Given the multiplicity of ligands for PTP-, the role of IL-34 regulation in these settings will need to be further defined.…”
Section: Discussionmentioning
confidence: 99%